ANISOTROPY AND HARDENABILITY OF INTERSTITIAL FREE STEELS UNDER THE INFLUENCE OF LOCALIZED DEFORMATION - Klejch, Filip; Schmidová, Eva; Mejtský, Tomáš (My University, 2022)
Interstitial Free (IF) steels are nowadays commonly used for stamping complex parts of outer automotive bodies. Current requirements for fast production lead to the need of monitoring the real state of the material after stamping based on its real material conditions. It is desirable to describe and quantify the evolution of microstructure deformation and plastic conditions before and after the stamping process. This paper presents Electron Backscatter Diffraction analyses of deformed and non-deformed IF steel, including the quantitative measurement of the localized plastic response of the real stamped part, using an unconventional indentation method. The effect of strain rate was evaluated using the highspeed tensile tests. The increased ratio of the Low Angle Grain Boundaries was found as a good parameter to quantify the depletion of plasticity.
ANISOTROPIE A DEFORMAČNÍ ZPEVNĚNÍ BEZINTERSTICIÁLNÍCH OCELÍ POD VLIVEM LOKALIZOVANÉ DEFORMACE
Keywords: interstitial free (IF) steel; local plastic response; real stamped part; high strain rate; microstructure analysis; Electron Backscatter Diffraction (EBSD); indentation; ocel bez intersticiálů (IF); lokální plastická odezva; výlisek; vysoká rychlost deformace; mikrostrukturní analýza; EBSD analýza; indentace